A pause in the weakening of the Atlantic meridional overturning circulation since the early 2010s - Sang-Ki Lee; Dongmin Kim; Fabian A. Gomez; Hosmay Lopez; Denis L. Volkov; Shenfu Dong; Rick Lumpkin; Stephen Yeager (Nature Communications)
Abstract The current state-of-the-art climate models when combined together suggest that the anthropogenic weakening of the Atlantic Meridional Overturning Circulation (AMOC) has already begun since the mid-1980s. However, continuous direct observational records during the past two decades have shown remarkable resilience of the AMOC. To shed light on this apparent contradiction, here we attempt to attribute the interdecadal variation of the historical AMOC to the anthropogenic and natural signals, by analyzing multiple climate and surface-forced ocean model simulations together with direct observational data. Our analysis suggests that an extensive weakening of the AMOC occurred in the 2000s, as evident from the surface-forced ocean model simulations, and was primarily driven by anthropogenic forcing and possibly augmented by natural variability. However, since the early 2010s, the natural component of the AMOC has greatly strengthened due to the development of a strong positive North Atlantic Oscillation. The enhanced natural AMOC signal in turn acted to oppose the anthropogenic weakening signal, leading to a near stalling of the AMOC weakening. Further analysis suggests that the tug-of-war between the natural and anthropogenic signals will likely continue in the next several years.